(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article investigates the problem of defining grammatical minimum in mother tongue education from corpus-based and competency-oriented perspectives. The study analyzes grammatical units used in general secondary education in terms of frequency, functionality, and contextual relevance, and substantiates methodological criteria for their selection. Using corpus analysis, comparative and statistical methods, the research demonstrates that grammatical minimum should be formed as a selective, functional, and pedagogically efficient system aligned with real communicative needs. The findings confirm that grammatical minimum should not be viewed as a closed set of rules, but as a system of functional units ensuring communicative competence. The results contribute to improving the practical effectiveness of grammar teaching.